2017
DOI: 10.3389/fpubh.2016.00296
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Care Continua: Lessons from HIV, Hepatitis C Virus, Tuberculosis and Implications for the Development of Improved Care and Prevention Continua

Abstract: BackgroundTo examine the application of continuum models to tuberculosis, HIV, and other conditions; to theorize the concept of continua; and to learn lessons that could inform the development of improved care and prevention continua as public health metrics.MethodsAn analytic review of literature drawn from several fields of health care.ResultsThe continuum construct is now part of public health evaluation systems for HIV, and is increasingly used in public health and the medical literature. Issues with the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 59 publications
0
58
0
1
Order By: Relevance
“…Shortening this period maximizes individual clinical benefit and reduces the risk of onward transmission, ultimately reducing both new infections and HIV‐related morbidity and mortality. Although the 90‐90‐90 targets and HIV care continua delineate important milestones, current metrics do not reflect the timeliness with which these key outcomes are achieved . In addition, in some settings, routine HIV viral load monitoring is infrequent, and pre‐ART CD4 count monitoring is declining in frequency with Treat All implementation , which limits opportunities to evaluate individual and public health impacts of HIV programming.…”
Section: Resultsmentioning
confidence: 99%
“…Shortening this period maximizes individual clinical benefit and reduces the risk of onward transmission, ultimately reducing both new infections and HIV‐related morbidity and mortality. Although the 90‐90‐90 targets and HIV care continua delineate important milestones, current metrics do not reflect the timeliness with which these key outcomes are achieved . In addition, in some settings, routine HIV viral load monitoring is infrequent, and pre‐ART CD4 count monitoring is declining in frequency with Treat All implementation , which limits opportunities to evaluate individual and public health impacts of HIV programming.…”
Section: Resultsmentioning
confidence: 99%
“…If the denominator is kept constant throughout sequential steps, the overall impact of cumulative losses is visually more apparent. If the numerator in the first step is taken as the denominator of the subsequent step, each step is essentially represented as a separate event and the impact of cumulative losses through sequential steps is visually de-emphasized 26 . Some studies represent these two approaches together, probably because they provide better information about the healthcare process, especially for viral load Cad.…”
Section: Variablesmentioning
confidence: 99%
“…One promising approach to addressing this challenge is the use of care cascades to identify points of loss, or gaps, in the chronic disease care continuum across screening, diagnosis, treatment, and control. Care cascades were originally used to model loss to follow up in HIV/AIDS care and have subsequently been applied to a range of other chronic conditions, including hypertension and diabetes [10,11]. Prior studies using data across multiple LMIC, for example, revealed large gaps between screening and diagnosis, with 80% unmet need in diabetes care [12][13][14].…”
Section: Introductionmentioning
confidence: 99%